DEVELOPMENT OF THE GAS TANKS OF THE NEW GENERATION, EQUIPPED WITH PROTECTIVE DEVICES FOR INCREASED POWER CONSUMPTION - Volkov, V. O.; Bubnov, V. M.; Bohomaz, H. I.; Kelrykh, M. B. (Science and Transport Progress, 2004)
The response and the stress-strain state of new generation gas tank-car design elements at emergency impacts in the head are investigated. The tank-car is equipped with tank head protection devices of safety shields with cellular energy absorbing element type. Efficiency of their use at emergency loading is shown.